Mitral Valve Surgery in Patients With Rheumatic Heart Disease: Repair vs. Replacement - Fu, Guangguo; Zhou, Zhuoming; Huang, Suiqing; Chen, Guangxian; Liang, Mengya; Huang, Lin; Wu, Zhongkai (Frontiers in Cardiovascular Medicine, 2021)
Background: High morbidity and mortality caused by rheumatic heart disease (RHD) are global burdens, especially in low-income and developing countries. Whether mitral valve repair (MVP) benefits RHD patients remains controversial. Thus, we performed a meta-analysis to compare the perioperative and long-term outcomes of MVP and mitral valve replacement (MVR) in RHD patients. Methods and Results: A systematic literature search was conducted in major databases, including Embase, PubMed, and the Cochrane Library, until 17 December 2020. Studies comparing MVP and MVR in RHD patients were retained. Outcomes included early mortality, long-term survival, freedom from reoperation, postoperative infective endocarditis, thromboembolic events, hemorrhagic events, and freedom from valve-related adverse events. Eleven studies that met the inclusion criteria were included. Of a total of 5,654 patients, 1,951 underwent MVP, and 3,703 underwent MVR. Patients who undergo MVP can benefit from a higher long-term survival rate (HR 0.72; 95% CI, 0.55–0.95; P = 0.020; I2 = 44%), a lower risk of early mortality (RR 0.62; 95% CI, 0.38–1.01; P = 0.060; I2 = 42%), and the composite outcomes of valve-related adverse events (HR 0.60; 95% CI, 0.38–0.94; P = 0.030; I2 = 25%). However, a higher risk of reoperation was observed in the MVP group (HR 2.60; 95% CI, 1.89–3.57; P<0.001; I2 = 4%). Patients who underwent concomitant aortic valve replacement (AVR) in the two groups had comparable long-term survival rates, although the trend still favored MVP. Conclusions: For RHD patients, MVP can reduce early mortality, and improve long-term survival and freedom from valve-related adverse events. However, MVP was associated with a higher risk of reoperation. Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=228307.